2022
DOI: 10.22161/jhed.4.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing different types of advertising and its influence on customer choice

Abstract: Marketers spend money on a variety of media platforms in order to influence consumer purchasing choice. Every advertisement on every media platform has a unique composition that engages the customers in a different way depending on the platform. The purpose of this research is to determine five types of advertisement and its influence on consumer purchasing choice at selected retailer stores in Erbil. It is a quantitative approach that is used to analyze data that has been obtained by the researcher. The Manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…A study by Ahakwa, Yang, Tackie and Bankole [13] also revealed that television advertisement has the greatest impact on customer purchase decision and was statistically significant at p< 0.01. The findings of this study are also similar to those of a study conducted by Qader, Hamza, Othman, Anwer, Hamad, Gardi, & Ibrahim, [14], where radio advertisements were found to have beneficial influence on the consumers. Radios have great socioeconomic influence on the consumers.…”
Section: Media Source Index Scores Showing Level Of Educative Value C...supporting
confidence: 90%
“…A study by Ahakwa, Yang, Tackie and Bankole [13] also revealed that television advertisement has the greatest impact on customer purchase decision and was statistically significant at p< 0.01. The findings of this study are also similar to those of a study conducted by Qader, Hamza, Othman, Anwer, Hamad, Gardi, & Ibrahim, [14], where radio advertisements were found to have beneficial influence on the consumers. Radios have great socioeconomic influence on the consumers.…”
Section: Media Source Index Scores Showing Level Of Educative Value C...supporting
confidence: 90%
“…That said, keep in mind that advertising can be a significant cost as well as annoying for audiences [29,30]. Further, advertising serves as a means often used by many marketers to generate awareness of the products and services they offer, with the ultimate goal of persuading consumers to make purchasing decisions [31,32]. It is important to recognize that advertising has a substantial influence in increasing consumer desire to buy a particular product or service.…”
Section: Advertisingmentioning
confidence: 99%
“…The second factor is advertising. Every advertisement on every media platform has a unique composition that engages the customers differently depending on the platform (Qader et al, 2022).…”
Section: Problem Statementmentioning
confidence: 99%